4D Seismic Analysis of Hydrocarbon Reservoir at Hugin Formation, Volve Field, North Sea - Agustin, Yasinta Farania; Lubis, Muhammad Husni Mubarak (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
This study investigates the 4D seismic analysis of oil-filled hydrocarbon reservoirs in the Volve Field. A primary objective is to model reservoir changes resulting from water injection activities using a time-lapse model-based inversion approach. The study employs Volve 3D seismic data from 2002 as a baseline and 2010 data as a monitor. Well logs used for the inversion include injection wells F-4 and F-5 and production well F-12. Inversion of the baseline and monitor seismic volumes reveals a distribution of acoustic impedance values ranging from 6770 to 12008 (m/s)*(g/cc). Time-lapse analysis, conducted by differencing the inverted baseline and monitor acoustic impedance volumes, reveals an average increase of approximately 2.74% in acoustic impedance in the vicinity of the injection and production wells. This increase is interpreted as a response to the migration of injected fluids into the reservoir. The spatial distribution of impedance changes suggests that the injected fluids preferentially migrate within the Middle Zone, rather than the Lower Hugin Zone. This behavior is likely controlled by the increased shale content in the Lower Hugin Zone, which acts as a permeability barrier and restricts downward fluid movement.